Sphingomonas paucimobilis Bloodstream Infection in a Post Liver Transplant Patient - Ekadashi Rajni; Anand Kumar Jain; Ayushi Jorwal; Naimish N. Mehta (Indian Journal of Transplantation)
The health-care sector has undergone remarkable progress along with experiencing challenges such as escalating antimicrobial resistance. Here, we report the successful management of Sphingomonas paucimobilis bloodstream infection in a postliver transplant patient. The objective of sharing this case report is to create the awareness regarding the possibility of this novel bug implicated in infections in the posttransplant setting. Further, it emphasizes on the utility of breakpoint to Minimum Inhibitory Concentration quotient in tailoring appropriate antibiotic therapy.